The Entamoeba histolytica Syf1 Homolog Is Involved in the Splicing of AG-Dependent and AG-Independent Transcripts - Torres-Cifuentes, Diana M.; Galindo-Rosales, José M.; Saucedo-Cárdenas, Odila; Valdés, Jesús (Frontiers in Cellular and Infection Microbiology, 2018)
Syf1 is a tetratricopeptide repeat (TPR) protein implicated in transcription elongation, spliceosome conformation, mRNA nuclear-cytoplasmic export and transcription-coupled DNA repair. Recently, we identified the spliceosomal components of the human parasite Entamoeba histolytica, among them is EhSyf. Molecular predictions confirmed that EhSyf contains 15 type 1 TPR tandem -antiparallel array motifs. Amoeba transformants carrying plasmids overexpressing HA-tagged or EhSyf silencing plasmids were established to monitor the impact of EhSyf on the splicing of several test Entamoeba transcripts. EhSyf Entamoeba transformants efficiently silenced or overexpressed the proteins in the nucleus. The overexpression or absence of EhSyf notably enhanced or blocked splicing of transcripts irrespective of the strength of their 3’ splice site. Finally, the absence of EhSyf negatively affected the transcription of an intron-less transcript. Altogether our data suggest that EhSyf is a bona fide Syf1 ortholog involved in transcription and splicing.